Vocabulary Coverage in the Listening Comprehension Texts in the New English Textbooks for Vietnamese High School Students: A Corpus-Based Investigation - Nguyen, Le Thanh Vy (Auckland University of Technology, 2023)
In the context of English as a foreign language (EFL) instruction, textbooks are of great importance in the classroom as the main source of lexical input for students. Consequently, it is crucial that textbooks adequately support students' overall comprehension and vocabulary acquisition, particularly with the most common English words. This study investigates the vocabulary load of a series of EFL textbooks used for Vietnamese high school students, focusing on the vocabulary coverage of high-frequency word-families, as well as that of 95% and 98% thresholds for text comprehension. To achieve these aims, a 9,849-word corpus has been created and then subjected to a frequency-based analysis of word families using the Vocabprofilers on the https://www.lextutor.ca/ website. The goal of this study is to evaluate a set of English textbooks used by Vietnamese high school students in order to: (1) establish the vocabulary load that students need to comprehend the listening comprehension sections of the textbooks; (2) to evaluate the coverage of high-frequency words in the listening texts, and (3) to examine how the lexical coverage varies between all units in the textbooks used for each grade. In addition, this study aims to offer a range of suggestions for English instructors in Vietnam and other EFL contexts for more successful textbook exploitation. As a result of the findings, it has been revealed that the students need to know 3,000 and 4,000 word-families to comprehend 95% and 98% of listening comprehension texts respectively. In addition, it has been found that the textbooks did not adequately represent the first and second 1,000-word lists. Moreover, the comparison between units in the textbooks used for each level shows a fluctuation in the lexical coverage. These findings emphasize the importance of the role of teachers in modifying textbooks for improved vocabulary acquisition and general comprehension of the materials.